Determination of Vitamin C (Ascorbic Acid) Content from Orange Fruit (Citrus reticulata Blanco) Based on Temperature and Storage Time - Yulia, Mega; Rahmi, Miftahur; Hilmarni, Hilmarni (Asian Journal of Pharmaceutical Research and Development, 2023)
The province of West Sumatera in Indonesia prioritizes three types of fruit: orange, mangosteen, and banana in its production every year. Orange fruit be one of the people favorite fruits because rich in vitamin C, good taste and affordable prices. There are various ways of storing orange fruit, some are stored in the refrigerator and some in room temperature, eaten directly or stored for several days. Based on that reasons research on vitamin C content in orange fruit based on temperature and storage time has been conducted. The objective of this research was to determine the effects of temperature (refrigeration temperature/8oC and room temperature/30oC) and storage time (1, 3 and 7 days) on vitamin C content in orange fruit. The orange fruit were squeezed, filtered and diluted 100 times. All prepared solution of orange fruit has been measured with uv-visible spectrophotometer at wavelength of maximum absorbance264 nm. The results revealed that is a decreased vitamin C content in orange fruit based on temperature and storage time. Where orange fruit are stored at room temperature decreased faster more than orange fruit that stored in refrigeration temperature and orange fruit with storage time 7 days have decreased more than orange fruit that stored for 3 days or 1 day. In conclusion is vitamin C content decreases accelerate with higher storage temperature and longer storage time.